Market Orientation, Transformational Leadership, Partnership Effects on Organizational Performance: A Competitive Advantage as a Mediator - Indra Muis; Puji Isyanto (Bina Nusantara University, 2021)
The research aimed to describe the implementation of market orientation, transformational leadership, and partnership strategy, competitive advantage, and organizational performance. It also analyzed the effects of the independent variables (market orientation, transformational leadership, and partnership strategy) and intervening variable (competitive advantage) on the dependent variable (organizational performance). The research applied a quantitative method. The respondents were 38 rectors or vice-rectors from private universities selected by using simple random sampling. The data were analyzed using PLS technique. The results show that all independent variables have positive effects on competitive advantage, except partnership strategy. Competitive advantage also has a positive effect on organizational performance. The practical research implication is that human resources in universities must have excellent service-oriented. They need to communicate well and coordinate to deliver better service to the students to be competitive and achieve better performance. In conclusion, to increase the university performance, the university leaders need to encourage all employees and faculty members to deliver the best service to the stakeholders of the universities and coordinate well across units to discuss issues and share ideas to solve the problems they have in service delivery. Then, the employees and faculty members will know what to improve and provide, and private universities will be much more competitive because of their reliable resources and capabilities.